Method for improving thermal stability of X type molecular sieve with low silica-alumina ratio
By forming a double-layer adsorption structure on the surface of the X-type molecular sieve with low silicon-aluminum ratio and undergoing phosphorus modification treatment, the problem of structural collapse and poor nitrogen-oxygen separation effect of molecular sieve under high temperature conditions is solved, and its thermal stability and nitrogen-oxygen are significantly improved Separation performance.
Patent Information
- Application Number
- CN202411829991.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-02-07
AI Technical Summary
The structure collapses when the low-silicon-aluminum ratio X-type molecular sieve is activated under high temperature conditions, the crystallinity decreases, and the nitrogen and oxygen separation effect is poor.
By placing Li-LSX molecular sieve in a macromolecular cationic surfactant solution for surface adsorption, a double-layer adsorption structure is formed to protect the skeleton structure of the molecular sieve and the Li+ in the pores, and then the phosphorus modification treatment is carried out in the phosphorus-containing solution to ensure phosphorus Ions are distributed only on the outer surface of the molecular sieve.
The thermal stability of the low silicon-aluminum ratio X-type molecular sieve is significantly improved, and its nitrogen-oxygen separation performance is maintained, avoiding the problems of structural collapse and crystallinity decline.
Smart Images

Figure CN119390086A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of preparation and modification of molecular sieve microporous materials, in particular to a method for improving the thermal stability of low silicon-aluminum ratio X-type molecular sieves. The molecular sieves prepared by the process are mainly used in the technical field of nitrogen-oxygen adsorption separation. Background Art
[0002] X-type molecular sieve is a faujasite zeolite (FAU) structure, with a silicon-aluminum ratio (SiO2 / Al2O3=2.0~3.0). The smaller the silicon-aluminum ratio of this molecular sieve, the more active sites and the higher the ion exchange performance. Conventionally, X-type molecular sieves with a silicon-aluminum ratio between 2.0 and 2.2 are called low silicon-aluminum ratio X-type molecular sieves (LSX molecular sieves). LSX molecular sieves are widely used as adsorbents and ion exchangers because of their high charge density and large pore size in the skeleton.
[0003] LSX molecular sieve has a low silicon-aluminum ratio and alumina tetrahedron [AlO2 - ] are more, in order to maintain the charge balance and stability of the zeolite framework, more cations (such as Na + , K + , Li + , Ca 2+ Mg 2+ ) to balance the negative charge on the framework, so LSX molecular sieve has more adsorption and ion exchange active sites. + The adsorption capacity of nitrogen by LSX molecular sieve (Li-LSX) after exchange is higher than that of Na + When the exchanged X molecular sieve is 50% higher, Li-LSX molecular sieve becomes an ideal pressure swing adsorbent and has been used in the field of nitrogen and oxygen adsorption separation to this day.
[0004] Research has found that only cations at the SII and SIII positions in the Li-LSX molecular sieve can contact with the adsorbate molecules and have a stronger force on the adsorbate molecules, resulting in better adsorption performance. + When the exchange degree is greater than 70%, the adsorption capacity of nitrogen by Li-LSX molecular sieve can increase rapidly. + When the exchange degree is greater than 96%, the nitrogen and oxygen separation coefficient (≥6.2) of the Li-LSX molecular sieve reaches the optimal value, and the nitrogen and oxygen separation effect is the best.
[0005] However, when Li-LSX molecular sieve is activated under high temperature conditions, it is very easy to cause the Al-O bond to break, and eventually the molecular sieve framework will be dealuminated, or even permanently inactivated. For example, when Li-LSX molecular sieve is activated at 450℃, the molecular sieve can still maintain 83% crystallinity, but if it is activated above 450℃, the crystallinity of Li-LSX molecular sieve will be greatly reduced, and the structure will collapse, thus affecting its ability to adsorb oxygen.
[0006] At present, the existing technology usually adopts Ca 2+ Mg 2+ Although the ion exchange modification of Li-LSX molecular sieve with rare earth ions can improve the thermal stability of the molecular sieve to a certain extent, its nitrogen and oxygen separation coefficient will decrease, and the nitrogen and oxygen separation effect is poor, which cannot meet the use requirements. Summary of the invention
[0007] The technical purpose of the present invention is to provide a method for improving the thermal stability of low silicon-aluminum ratio X-type molecular sieves, so as to solve the problems of structural collapse, decreased crystallinity and poor nitrogen-oxygen separation effect of existing low silicon-aluminum ratio X-type molecular sieves during high-temperature activation.
[0008] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for improving the thermal stability of low silicon-aluminum ratio X-type molecular sieve, comprising the following steps: (1) Li-LSX molecular sieve raw powder is placed in a macromolecular cationic surfactant solution, and the Li-LSX molecular sieve is allowed to reach surface adsorption saturation under continuous stirring conditions, and then filtered and washed; (2) The solid material obtained after washing in step (1) is placed in a phosphorus-containing solution and subjected to phosphorus modification treatment under continuous stirring. After filtering, washing, drying and calcining to remove the surfactant, a low silicon-aluminum ratio X-type molecular sieve with significantly improved thermal stability is obtained.
[0009] Furthermore, in step (1), the chemical composition of the Li-LSX molecular sieve raw powder is xLi2O.yNa2O.Al2O3.nSiO2, wherein 0.7≤x≤1.0, 0.0≤y≤0.3, 2.0≤n≤2.2, and its BET specific surface area is 400-1000m 2 / g, and the average pore size is 0.3-3.0nm.
[0010] Furthermore, in step (1), the macromolecular cationic surfactant is at least one of cetyltrimethylammonium bromide, cetyltrimethylammonium chloride and cetyltrimethylammonium hydroxide.
[0011] Furthermore, in step (1), the concentration of the macromolecular cationic surfactant solution is 0.001 to 0.1 mol / L.
[0012] Furthermore, in step (1), the mass ratio between the Li-LSX molecular sieve raw powder and the macromolecular cationic surfactant solution is 1: (10-100), the treatment temperature during surface adsorption is 20-50° C., and the treatment time is 12-48 hours.
[0013] Furthermore, in step (1) and step (2), the solution used for washing is deionized water.
[0014] Furthermore, in step (2), the phosphorus source in the phosphorus-containing solution is at least one of phosphoric acid, ammonium phosphate, aluminum phosphate, ammonium dihydrogen phosphate and diammonium hydrogen phosphate.
[0015] Furthermore, in step (2), the concentration of the phosphorus-containing solution is 0.01-1.0 mol / L.
[0016] Furthermore, in step (2), the solid-liquid mass ratio during the phosphorus modification treatment is 1:(10-100), the treatment temperature is 20-50° C., and the treatment time is 12-48 hours.
[0017] Furthermore, in step (2), the drying temperature is 90-150° C., the drying time is 5-10 hours, the calcination temperature is 400-500° C., and the calcination time is 3-6 hours.
[0018] Beneficial effects: The method for improving the thermal stability of low silicon-aluminum ratio X-type molecular sieve of the present invention comprises the following steps: firstly, a macromolecular cationic surfactant is saturated with the Li-LSX molecular sieve to form a double-layer adsorption structure on the outer surface of the molecular sieve, and the framework structure of the molecular sieve and the Li in the pores are saturated with the adsorption of the macromolecular cationic surfactant. + The zeolite is then placed in a phosphorus-containing solution to allow phosphorus ions to adsorb only on macromolecular cationic surfactants, and then the surfactants are removed by calcination, so that phosphorus is only distributed on the outer surface of the zeolite without destroying the framework structure of the Li-LSX molecular sieve and the Li + Compared with the Li-LSX molecular sieve before modification, its advantages are mainly reflected in: 1. The present invention will not affect the framework structure of Li-LSX molecular sieve and Li + The damage will not reduce the nitrogen and oxygen separation performance of the molecular sieve, but it can significantly improve the thermal stability of the molecular sieve. The test results show that the phosphorus-modified Li-LSX molecular sieve prepared by the present invention has similar crystallinity and nitrogen and oxygen separation performance as the Li-LSX molecular sieve. The comparative data are as follows: Figure 1 And as shown in Table 1.
[0019] 2. The phosphorus-modified Li-LSX molecular sieve prepared by the present invention is activated in the temperature range of 30-800°C, the structure remains stable, and the thermal stability is greatly improved. The comparative data are as follows Figure 2 .
[0020] 3. The water absorption rate of the phosphorus-modified Li-LSX molecular sieve prepared by the present invention is significantly lower than that of the Li-LSX molecular sieve, the sensitivity to water is reduced, the hydrophobicity is increased, the storage conditions for the adsorbent are reduced, and the operability is improved. The comparative data are as follows: Figure 3 shown. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 XRD spectra of phosphorus-modified Li-LSX molecular sieve and Li-LSX molecular sieve; Figure 2 It is the differential thermal analysis spectrum of phosphorus modified Li-LSX type molecular sieve and Li-LSX type molecular sieve; Figure 3 It is the static saturated water adsorption diagram of phosphorus-modified Li-LSX molecular sieve and Li-LSX molecular sieve; Figure 4 This is a statistical table of nitrogen and oxygen adsorption and separation coefficients of phosphorus-modified Li-LSX molecular sieves and Li-LSX molecular sieves. DETAILED DESCRIPTION
[0022] The specific embodiments of the present invention are described in detail below, but it should be understood that the protection scope of the present invention is not limited by the specific embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the protection scope of the present invention. The experimental methods in the embodiments of the present invention are conventional methods unless otherwise specified.
[0023] A method for improving the thermal stability of a low silicon-aluminum ratio X-type molecular sieve comprises the following steps: (1) Place the Li-LSX molecular sieve raw powder in a macromolecular cationic surfactant solution, stir continuously until adsorption equilibrium is reached, filter, and wash; The chemical composition of Li-LSX molecular sieve raw powder is xLi2O.yNa2O.Al2O3.nSiO2, where 0.7≤ x≤1.0, 0.0≤ y ≤0.3, 2.0≤ n ≤2.2, and its BET specific surface area is 400-1000m 2 / g, an average pore size of 0.3-3.0nm; the macromolecular cationic surfactant is at least one of cetyltrimethylammonium bromide, cetyltrimethylammonium chloride and cetyltrimethylammonium hydroxide; the concentration of the macromolecular cationic surfactant solution is 0.001-0.1mol / L; the mass ratio between the Li-LSX molecular sieve raw powder and the macromolecular cationic surfactant solution is 1:(10-100), the treatment temperature during surface adsorption is 20-50°C, and the treatment time is 12-48h; the solution used for washing is deionized water.
[0024] (2) placing the sample obtained in step (1) in a phosphorus-containing solution, stirring continuously, filtering, washing, drying, and calcining to remove the surfactant, thereby obtaining a low silicon-aluminum ratio X-type molecular sieve with significantly improved thermal stability; The phosphorus source in the phosphorus-containing solution is at least one of phosphoric acid, ammonium phosphate, aluminum phosphate, ammonium dihydrogen phosphate and diammonium hydrogen phosphate; the concentration of the phosphorus-containing solution is 0.01-1.0 mol / L; the solid-liquid mass ratio during phosphorus modification treatment is 1: (10-100), the treatment temperature is 20-50°C, and the treatment time is 12-48h; the solution used for washing is deionized water, the drying temperature is 90-150°C, the drying time is 5-10h, the calcination temperature is 400-500°C, and the calcination time is 3-6h.
[0025] The present invention provides a method for improving the thermal stability of a low silicon-aluminum ratio X-type molecular sieve. The macromolecular cationic surfactant used in the process is an organic macromolecular compound with an ammonium group, which mainly acts on the surface of the Li-LSX molecular sieve to protect the internal pores and prevent phosphoric acid from entering the pores and causing blockage. The method does not affect the skeleton structure and Li + It will not cause damage, but will not cause a serious decline in the nitrogen and oxygen separation performance of the Li-LSX molecular sieve before modification, but it can significantly improve the thermal stability of the molecular sieve, and has a good practical effect.
[0026] Example 1 A method for improving the thermal stability of a low silicon-to-aluminum ratio X-type molecular sieve according to the present embodiment specifically comprises the following steps: (1) Mix 5 g of Li-LSX molecular sieve powder with 100 mL of 0.001 mol / L hexadecyltrimethylammonium bromide solution, stir at 20 °C for 48 hours to reach adsorption equilibrium, filter, and wash; (2) The sample obtained in step (1) was mixed with 100 mL of 0.01 mol / L phosphoric acid solution, stirred at 20°C for 48 hours, filtered, washed, dried at 90°C for 10 hours, and then calcined at 400°C for 6 hours to obtain a low silicon-aluminum ratio X-type molecular sieve with significantly improved thermal stability, denoted as PLi-LSX-1.
[0027] Example 2 A method for improving the thermal stability of a low silicon-to-aluminum ratio X-type molecular sieve according to the present embodiment specifically comprises the following steps: (1) Mix 5 g of Li-LSX molecular sieve powder with 80 mL of 0.01 mol / L hexadecyltrimethylammonium chloride solution, stir at 30 °C for 24 hours to reach adsorption equilibrium, filter, and wash; (2) The sample obtained in step (1) was mixed with 80 mL of 0.1 mol / L ammonium phosphate solution, stirred at 30°C for 24 hours, filtered, washed, dried at 120°C for 6 hours, and then calcined at 450°C for 4 hours to obtain a low silicon-aluminum ratio X-type molecular sieve with significantly improved thermal stability, denoted as PLi-LSX-2.
[0028] Example 3 A method for improving the thermal stability of a low silicon-to-aluminum ratio X-type molecular sieve according to the present embodiment specifically comprises the following steps: (1) Mix 5 g of Li-LSX molecular sieve powder with 50 mL of 0.05 mol / L hexadecyltrimethylammonium hydroxide solution, stir at 40 °C for 12 hours to reach adsorption equilibrium, filter, and wash; (2) The sample obtained in step (1) was mixed with 50 mL of 0.5 mol / L diammonium hydrogen phosphate solution, stirred at 40°C for 12 hours, filtered, washed, dried at 150°C for 5 hours, and then calcined at 500°C for 3 hours to obtain a low silicon-aluminum ratio X-type molecular sieve with significantly improved thermal stability, recorded as PLi-LSX-3.
[0029] Example 4 A method for improving the thermal stability of a low silicon-to-aluminum ratio X-type molecular sieve according to the present embodiment specifically comprises the following steps: (1) Mix 5 g of Li-LSX molecular sieve powder with 50 mL of 0.1 mol / L hexadecyltrimethylammonium hydroxide solution, stir at 50 °C for 12 hours to reach adsorption equilibrium, filter, and wash; (2) The sample obtained in step (1) was mixed with 50 mL of 1.0 mol / L diammonium phosphate solution, stirred at 50° C. for 12 hours, filtered, washed, dried at 150° C. for 5 hours, and then calcined at 500° C. for 3 hours to obtain a low silicon-aluminum ratio X-type molecular sieve with significantly improved thermal stability, denoted as PLi-LSX-4.
[0030] Test determination The phosphorus-modified Li-LSX molecular sieves prepared in Examples 1 to 4 of the present invention and the raw material Li-LSX molecular sieves were subjected to XRD measurement, and the results are shown in the attached figure. Figure 1 shown.
[0031] from Figure 1 It can be seen that the structure of the LSX molecular sieve is not destroyed before and after phosphorus modification.
[0032] The phosphorus-modified Li-LSX molecular sieves prepared in Examples 1 to 4 of the present invention and the raw material Li-LSX molecular sieves were subjected to differential thermal analysis. The obtained differential thermal analysis spectra are as follows: Figure 2 shown.
[0033] from Figure 2 It can be seen that the Li-LSX type zeolite shows an obvious exothermic peak after 450°C, indicating that the structure of the zeolite collapses at this time; while the phosphorus-modified Li-LSX type zeolite still does not show an exothermic peak at 800°C, indicating that the structure of the zeolite can still remain stable at this time without collapse.
[0034] The hydrophobicity of the phosphorus-modified Li-LSX molecular sieves prepared in Examples 1 to 4 of the present invention and the raw material Li-LSX molecular sieves was tested and placed in static saturated water for adsorption. The static saturated water adsorption diagram is shown in FIG. Figure 3 shown.
[0035] from Figure 3 It can be seen that the water absorption rate of the phosphorus-modified low silicon-aluminum ratio X-type molecular sieve is significantly lower than that of the Li-LSX type molecular sieve, and its sensitivity to water is reduced and its hydrophobicity is increased.
[0036] The nitrogen and oxygen adsorption performance of the phosphorus-modified Li-LSX molecular sieves prepared in Examples 1 to 4 of the present invention and the raw material Li-LSX molecular sieves were tested. The test results are as follows: Figure 4 shown.
[0037] from Figure 4 It can be seen that the nitrogen and oxygen separation coefficient of the Li-LSX molecular sieve is 6.30, and the nitrogen and oxygen separation coefficient of the phosphorus-modified Li-LSX molecular sieve can reach 6.23-6.28, which meets the requirements of industrial application (nitrogen and oxygen separation coefficient ≥ 6.2), proving that the process method of the present invention will not cause a serious decline in the nitrogen and oxygen separation performance of the Li-LSX molecular sieve, but can significantly improve the thermal stability of the molecular sieve.
Claims
1. A method for improving the thermal stability of low silicon-aluminum ratio X-type molecular sieve, characterized in that: The steps include: (1) Li-LSX molecular sieve raw powder is placed in a macromolecular cationic surfactant solution, and the Li-LSX molecular sieve is allowed to reach surface adsorption saturation under continuous stirring conditions, and then filtered and washed; (2) The solid material obtained after washing in step (1) is placed in a phosphorus-containing solution and subjected to phosphorus modification treatment under continuous stirring. After filtering, washing, drying and calcining to remove the surfactant, a low silicon-aluminum ratio X-type molecular sieve with significantly improved thermal stability is obtained.
2. A method for improving the thermal stability of a low silicon-aluminum ratio X-type molecular sieve according to claim 1, characterized in that: In step (1), the chemical composition of the Li-LSX molecular sieve raw powder is xLi2O.yNa2O.Al2O3.nSiO2, wherein 0.7≤x≤1.0, 0.0≤y≤0.3, 2.0≤n≤2.2, and its BET specific surface area is 400-1000m 2 / g, and the average pore size is 0.3-3.0nm.
3. The method for improving the thermal stability of low silicon-aluminum ratio X-type molecular sieve according to claim 1, characterized in that: In step (1), the macromolecular cationic surfactant is at least one of cetyltrimethylammonium bromide, cetyltrimethylammonium chloride and cetyltrimethylammonium hydroxide.
4. The method for improving the thermal stability of low silicon-aluminum ratio X-type molecular sieve according to claim 1, characterized in that: In step (1), the concentration of the macromolecular cationic surfactant solution is 0.001-0.1 mol / L.
5. A method for improving the thermal stability of a low silicon-aluminum ratio X-type molecular sieve according to claim 1 or 4, characterized in that: In step (1), the mass ratio between the Li-LSX molecular sieve raw powder and the macromolecular cationic surfactant solution is 1: (10-100), the treatment temperature during surface adsorption is 20-50° C., and the treatment time is 12-48 hours.
6. The method for improving the thermal stability of low silicon-aluminum ratio X-type molecular sieve according to claim 1, characterized in that: In step (1) and step (2), the solution used for washing is deionized water.
7. The method for improving the thermal stability of low silicon-aluminum ratio X-type molecular sieve according to claim 1, characterized in that: In step (2), the phosphorus source in the phosphorus-containing solution is at least one of phosphoric acid, ammonium phosphate, aluminum phosphate, ammonium dihydrogen phosphate and diammonium hydrogen phosphate.
8. A method for improving the thermal stability of a low silicon-aluminum ratio X-type molecular sieve according to claim 1 or 7, characterized in that: In step (2), the concentration of the phosphorus-containing solution is 0.01-1.0 mol / L.
9. A method for improving the thermal stability of low silicon-aluminum ratio X-type molecular sieve according to claim 8, characterized in that: In step (2), the solid-liquid mass ratio during the phosphorus modification treatment is 1:(10-100), the treatment temperature is 20-50°C, and the treatment time is 12-48h.
10. The method for improving the thermal stability of low silicon-aluminum ratio X-type molecular sieve according to claim 1, characterized in that: In step (2), the drying temperature is 90-150°C, the drying time is 5-10 hours, the calcination temperature is 400-500°C, and the calcination time is 3-6 hours.